(untitled) (Acta Scientiarum. Agronomy, 2018)
Image analysis using X-rays is an efficient technique for assessing the seed quality of several species, presenting itself as a rapid response method that is simple to execute, reproducible and non-destructive. Thus, this research adjusted a methodology that aims to relate the internal morphology of broccoli seeds to their physiological potential through radiographic analysis of seeds and computerized images of seedlings. The broccoli cultivars used were Piracicaba Precoce and Ramoso Santana represented by ten lots of each one. The study was conducted using X-ray imaging for seed analysis, in which the area, density and circularity measures were obtained as internal morphology characteristics of seeds. After a germination test, the seedling length was obtained 5 days after sowing. Multivariate analysis was carried out using principal components analysis. It was concluded that the X-ray test is efficient for evaluating the internal morphology of broccoli seeds and associating it with seedling length, thereby classifying seed lots at different levels of vigor.